External corporate governance and financial fraud: cognitive evaluation theory insights on agency theory prescriptions. (27th October 2016) - Shi, Wei; Connelly, Brian L.; Hoskisson, Robert E.
Abstract : R esearch summary : Agency theory suggests that external governance mechanisms (e.g., activist owners, the market for corporate control, securities analysts) can deter managers from acting opportunistically. Using cognitive evaluation theory, we argue that powerful expectations imposed by external governance can impinge on top managers' feelings of autonomy and crowd out their intrinsic motivation, potentially leading to financial fraud. Our findings indicate that external pressure from activist owners, the market for corporate control, and securities analysts increases managers' likelihood of financial fraud. Our study considers external governance from a top manager's perspective and questions one of agency theory's foundational tenets: that external pressure imposed on managers reduces the potential for moral hazard . M anagerial summary : Many of us are familiar with stories about top managers "cooking the books" in one way or another. As a result, companies and regulatory bodies often implement strict controls to try to prevent financial fraud. However, cognitive evaluation theory describes how those external controls could actually have the opposite of their intended effect because they rob managers of their intrinsic motivation for behaving appropriately. We find this to be the case. When top managers face more stringent external control mechanisms, in the form of activist shareholders, the threat of a takeover, or zealous securities analysts, they are actually more likely to engage in financial misbehavior . Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Video Abstract